2019
DOI: 10.3390/app9183713
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis of Knee Ligaments in the Landing Phase of Freestyle Skiing Aerial

Abstract: The risk of knee injuries in freestyle skiing athletes that perform aerials is high. The internal stresses in the knee joints of these athletes cannot easily be directly measured. In order to ascertain the mechanical response of knee joints during the landing phase, and to explore the mechanism of damage to the cartilage and ligaments, a finite element model of the knee joint was established. Three successful landing conditions (neutral, backward, or forward landing) from a triple kicker were analyzed. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Excess weight may lead to reduced agility and smoothness in their movements. In addition, the impact on the knee joint is greater when landing, and the risk of injury will increase [ 17 ]. In summary, the weight of aerials athletes must be controlled within the ideal range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess weight may lead to reduced agility and smoothness in their movements. In addition, the impact on the knee joint is greater when landing, and the risk of injury will increase [ 17 ]. In summary, the weight of aerials athletes must be controlled within the ideal range.…”
Section: Discussionmentioning
confidence: 99%
“…This increases the risk of injury to the joint cartilage, menisci, subchondral bone, and ligaments. Locking athletes’ ankles in ski boots diminishes cushioning and amplifies impact forces on knee joints during landing [ 17 ]. The cold and variable outdoor environment further increases the risk of injury to athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Contributions can focus on sensors, wearable hardware, algorithms, or integrated monitoring systems. We organized the different papers according to their contributions to the main parts of the monitoring and control engineering scheme applied to human health applications, namely papers focusing on measuring/sensing of physiological variables [24][25][26][27][28][29][30][31], contributions describing research on the modelling of biological signals [32][33][34][35][36][37][38], papers highlighting health monitoring applications [39][40][41][42], and finally examples of control applications for human health [43][44][45][46][47][48]. In comparison to biomedical engineering, we envision that the field of human health engineering also covers applications on healthy humans (e.g., sports, sleep, and stress) and thus not only contributes to develop technology for curing patients or supporting chronically ill people, but also for disease prevention and optimizing human well-being more generally.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
“…Such a model-based approach has especially clinical relevance for screening patients for COPD using classical spirometry in primary care. In their work, Fu et al [33] developed a mechanistic finite element model to simulate forces and stresses inside knee joints during the landing phase in freestyle skiing aerial. These simulations helped quantifying which types of landings are most challenging in terms of ligament damage.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
“…Landing failure will not only affect the total score but also cause sports injuries. For example, the rate of knee joint injury in aerials athletes on the Chinese national team is close to 85% and higher in retired athletes ( Fu et al, 2019 ). Studies have shown that instantaneous impact in the vertical direction will damage the cartilage of the knee joint, while the long-term repeated impact will cause strain damage to the stress concentration region of the cartilage ( Meng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%